Rh–Ag–Si ternary composites: highly active hydrogen evolution electrocatalysts over Pt–Ag–Si. Issue 4 (4th January 2017) - Jiang, Binbin; Sun, Yuyang; Liao, Fan; Shen, Wen; Lin, Haiping; Wang, Hui; Shao, Mingwang
Abstract : Rh–Ag–Si ternary catalysts exhibit more active hydrogen evolution performance than Pt–Ag–Si based on the theoretical calculation and experimental results. Abstract : Hydrogen production with the aid of electrocatalysis is a critical component for several developing clean-energy technologies. Such a renewable energy depends heavily on the choice of cheap and efficient catalysts for hydrogen evolution, which has still been a challenge until now. In this work, the theoretical calculation indicates that Rh–Ag–Si ternary catalysts exhibit more active hydrogen evolution performance than Pt–Ag–Si because the migration activation energies of H atoms from Rh(111) to Si are lower than those from Pt(111) to Si via the Ag surface. This simulation was confirmed by the experimental results: Rh–Ag/SiNW (or Pt–Ag/SiNW) catalysts were prepared by directly reducing Rh (or Pt) and Ag ions with Si–H bonds. The Rh–Ag/SiNW-2 with the optimal mass ratio of 2.3 : 23.4 : 74.3 (Rh : Ag : Si) exhibited a lower Tafel slope (51 mV dec −1 ) and a larger exchange current density (87.1 × 10 −6 A cm −2 ) than the Pt–Ag/SiNW. In addition, the mass activity of Rh–Ag/SiNW-2 at an overpotential of 0.2 V (11.5 mA μgRh −1 ) is 12.0, 5.0 and 3.3 fold higher than that of Rh–Ag (0.96 mA μgRh −1 ), Pt–Ag/SiNW (2.3 mA μgPt −1 ) and 40 wt% Pt/C (3.5 mA μgPt −1 ) catalysts, respectively. Moreover, the Rh–Ag/SiNW nanocatalysts had good stability in acidic media. The results presented herein may offer a novel and effective methodology for the designing of cost-efficient and environmentally friendly catalysts for electrochemical fields.